ANALISIS PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN MOTOR GESITS PADA PT. ARKEN EHOWU PUTRA MOTOR KOTA GUNUNGSITOLI - Eferlin Gulo; Yuterlin Zalukhu; Maria Magdalena Bate’e; Otanius Laia (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
This study aims to analyze consumer behavior in making purchasing decisions for Gesits motorbikes at PT. Arken Ehowu Putra Motor in Gunugsitoli City. With the increasing attention to environmentally friendly vehicles, Gesits motorbikes, as one of the electric vehicles, are the main focus of this study. The research methods used include surveys and in-depth interviews to evaluate factors that influence purchasing decisions, such as price, performance, technical features, and brand image. The results of the study indicate that consumers in Gunugsitoli City are very important considerations. In addition, product constraints and after-sales support also play an important role in purchasing decisions. These findings indicate that PT. Arken Ehowu Putra Motor needs to focus on delivering clear information about the long-term benefits of Gesits motorbikes and improving the quality of after-sales services to meet consumer expectations and increase customer satisfaction.